An Unusual Initial Presentation of Lupus Nephritis as a Renal Mass - Remi Goupil; Annie-Claire Nadeau-Fredette; Virginie Royal; Alexandre Dugas; Jean-Philippe Lafrance (Case Reports in Nephrology)
Lupus nephritis is a frequent manifestation of systemic lupus erythematous. Lupus nephritis usually presents with abnormal urinalysis, proteinuria, and/or renal insufficiency. We report a case of a 48-year-old woman who underwent partial nephrectomy for a fortuitously discovered solid enhancing left kidney mass. No neoplastic cells were found in the biopsy specimen; however, the pathology findings were compatible with immune complex glomerulonephritis with a predominantly membranous distribution, a pattern suggestive of lupus nephritis. The mass effect was apparently due to a dense interstitial lymphocytic infiltrate resulting in a pseudotumor. Further investigation revealed microscopic hematuria with a normal kidney function and no significant proteinuria. Antinuclear antibodies were negative, although anti-DNA and anti-SSA/Rho antibodies were positive. A diagnosis of probable silent lupus nephritis was made and the patient was followed up without immunosuppressive treatment. After two years of follow-up, she did not progress to overt disease. To our knowledge, this represents the first case of lupus nephritis with an initial presentation as a renal mass.